2021
DOI: 10.21203/rs.3.rs-168652/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling Oscillations in the Supply Chain: The Case of a Just-in-Sequence Supply Process from the Automotive Industry

Abstract: Pervasive and ubiquitous oscillations, mapping the repetitive variation in time of a specific state, are well known as abundant phenomena in research and practice. Motivated by the success of oscillators in the modelling, analysis and control of dynamical systems, we developed a related approach for the dynamic description of supply chains. This paper aims to introduce a generic oscillator model for supply chains by the original application of oscillator equations. Therefore an established oscillator model for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It was found that energy decreases as travelers stay on their current routes, which is analogous to the damping of an oscillator. Klug (2022) recently published an oscillatory model for supply chains. Two coupled van der Pol oscillators were used to model and control the dynamical interaction of an inventory system.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that energy decreases as travelers stay on their current routes, which is analogous to the damping of an oscillator. Klug (2022) recently published an oscillatory model for supply chains. Two coupled van der Pol oscillators were used to model and control the dynamical interaction of an inventory system.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Summarizing our literature review, we have found very few examples of the application of a generic oscillating model in transportation science. These were either generally designed for supply networks (Donner et al, 2007; Helbing et al, 2004) or very specifically (Xiao et al, 2016) for the consideration of travelers' choice decisions or inventory control (Klug, 2022). Therefore, our goal was to develop a general approach for the evaluation of the synchronization phenomena to support the planning and operation of transportation networks.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%